Effect of Fast Dissolved Phosphorus Fertilizer on the Growth, Seed Product, and Phosphorus Uptake Efficiency of Soybean (Glycine max L.) - Cahyono, Ongko; Minardi, Slamet (AGRIVITA, Journal of Agricultural Science, 2022)
The appropriate method of P fertilizer application is very important for the efficiency of P uptake and yield improvement. This research aimed to assess the growth response, seed product, and P uptake efficiency of soybean to the application of fast dissolved phosphorus fertilizer. Two consecutive potted experiments under greenhouse condition were conducted using Alfisols from Jumantono Karanganyar as planting media. The soybeans were planted and treated with six doses of P fertilizer. The treatments were designed in a completely randomized experiment with 5 replications. In the first experiment, the plants were harvested at the maximum vegetative growth for measurement of plant growth components and P uptake. In the second experiment, the plants were harvested at optimum grain maturity for seed yield and P efficiency measurements. The results showed that the application of fast dissolved-P fertilizer improved plant growth, seed yield and P uptake efficiency. Fast dissolved-P fertilizer was optimum at a dose of 100 kg/ha which was applied in a split application method at 0, 15, and 30 days after planting. However further field research is necessary to confirm the results.